Two-stage planning method of distributed generation for improvement of resilience in extreme weather based on load partition coordinated recovery - Gu, Jiting; Wang, Shuai; Ou, Yangbo (Frontiers in Energy Research, 2023)
In extreme weather, distributed generation can support the black-start of the power grid. In this paper, a two-stage planning method of distributed generation for improvement of resilience in extreme weather based on coordinated recovery of load partition is proposed. Firstly, scenario generation model, including the distributed generation output and line failure models, is established to obtain the power output and line status in different scenarios with different weather. Then, an optimal sub-network screening robust optimization model is built as the first stage model to screen the optimal sub-networks for the deployment of distributed generation in each scenario. Finally, a node location optimization model was developed as a second stage model to obtain the optimal node locations for deploying distributed generation within the sub-network, which aims at maximizing the recovery efficiency of critical loads. Case studies based on modified IEEE 30-bus system are used to demonstrate the effectiveness of the proposed method. The findings show that the recovered load and recovery efficiency of power system can be improved significantly.